Low Rate of babA2 Genotype among Iranian Helicobacter pylori Clinical Isolates - Sohrabi, Maryam (J Clin Diagn Res, 2017)
INTRODUCTION: The Blood Group Antigen-Binding Adhesion (babA), Outer Inflammatory Protein (oipA) and Sialic Acid-Binding Adhesin (sabA) as outer membrane proteins involved in Helicobacter pylori adherence to gastric mucosa have been suggested to have a role in the pathogenesis. AIM: To investigate the frequency of H. pylori isolates babA2, oipA and sabA genes in Iranian dyspeptic patients. MATERIALS AND METHODS: DNAs were extracted from H. pylori –positive cultures taken from 100 different dyspeptic patients. Genotyping was performed by Polymerase Chain Reaction (PCR), using the specific primers for babA2, oipA and sabA genes. Chi square test was used to investigate association between variables, p<0.05 was considered statistically significant. RESULTS: All (100%) isolates possessed oipA and sabA genotypes, whereas babA2 was detected in 22% of isolates. There was no significant relationship between presence of genes with clinical outcome. The combined genotype oipA +/sabA +/ babA2- was correlated with gastritis. The rate of babA2 genotype in our isolates was lower than other Iranian reports. CONCLUSION: Frequency of babA2 genotype among H. pylori isolates from Southwest of Iran is considerably less than other regions of Iran. Due to heterogeneity of H. pylori strains in different geographic regions, further work will be needed to understand the role of these virulence genes in H. pylori pathogenesis and their possible association with disease outcome.